Welfare over Warfare? Russia’s War on Ukraine through the Prism of Europe’s Energy Security - Baranowski, Mariusz (International Journal of Energy Economics and Policy, 2022)
The outbreak of war by the Russian Federation in Ukraine on 24 February 2022 not only took world public opinion and politicians by surprise but, above all, demonstrated in all its glory the strong network of political and economic ties in Europe and far beyond the old continent. The attitudes of individual governments and entire societies, particularly in Europe, towards Russian aggression, differ fundamentally. These differences can most simply be explained in terms of economic and political dependence on Russian gas or proximity to the Russian Federation or its dependent countries like Belarus, which mark sharp dividing axes. In this paper, using a survey commissioned by the European Council on Foreign Relations in ten European countries as an example, I will highlight public attitudes towards the war in Ukraine and their potential impact on the policies of individual governments. The interventionist viewpoint presented in this article suggests that general welfare shapes not only public attitudes towards the war but also impregnates specific governmental positions. In the context of the large European economies, this could significantly yet negatively impact Ukraine's financial and military support in the coming months.